Case Report: A rare case of a giant sporadic non-ampullary duodenal adenoma that was safely and effectively resected using hybrid endoscopic submucosal dissection - Jun-Jie Hou; Liang Ding; Yan-Fei Yang; Wei-Wei Li (Frontiers in Oncology)
BackgroundAs a rare condition, sporadic non-ampullary duodenal adenomas (SNADAs) are typically asymptomatic and diagnosed incidentally. It warrants treatment due to the high risk of malignant transformation. However, giant SNADAs, especially those treated using hybrid endoscopic submucosal dissection (ESD), are exceedingly rare, and to our knowledge, this condition has not been reported previously.Case presentationA 69-year-old Chinese male patient was diagnosed with an incidentally discovered giant SNADA. Given the size and location and the patient’s non-invasive request, we performed hybrid ESD to completely resect a giant SNADA (4.5*2.8*1.0cm) without postoperative discomfort or complications. Final pathology confirmed a margin-negative tubulovillous adenoma with low-grade intraepithelial neoplasia.ConclusionWe present a rare case of a giant SNADA that was successfully dissected using hybrid ESD. Further, we provide a brief review, discuss the treatment protocol of this case, and provide a new perspective for the future diagnosis and treatment of a giant SNADA.